Método primal-dual previsor-corretor de pontos interiores e exteriores com estratégias de correção de inércia e suavização hiperbólica aplicado ao problema de despacho econômico com ponto de carregamento de válvula e representação da transmissão - Silva, Diego Nunes da [UNESP] (2014)
In the economic dispatch problem, the objective is to determine the active power output of the generating units in order to supply the demand and minimize the fuel costs associated with power generation, while talking into account system operational constraints. The cost objective function of this problem can be defined in many different ways, but a more realistic form of representation includes valve-point load effects. When valve-point load effects are considered, the objective function becomes non-differentiable, which precludes the direct application of classical optimization methods to solve the problem. For this reason, most proposals to solve the Economic Dispatch Problem with Valve-Point Load Effects (EDP-VPE) available in the literature are based on heuristics. In this work, we present a Primal-Dual Predictor-Corrector Modified Logarithmic Barrier method (PDPCMLB) associated with an inertia correction strategy and a hyperbolic smoothing technique to solve economic dispatch problems with valve-point load effects. The purpose of the inertia correction is to ensure that the proposed method converges to a local minimum of the problem. The hyperbolic smoothing technique, when applied to the EDP-VPE and its variations - the Economic Dispatch Problem with Loss Representation and Valve-Point Load Effects (EDP-LVPE) and the Network Constrained Economic Dispach with Valve-Point Load Effects (NC-EDP-VPE) -, allows the use of the PDPCMLB method to solve it. An implementation of these methods, performed in Matlab, shows that they are efficient to solve the EDP-VPE and its variations, obtaining good results whem compared to athers available in the literature